2017
DOI: 10.23834/isrjournal.341694
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Service Quality, Customer Satisfaction and Behavioral Intentions in Airline Industry: A SEM Approach

Abstract: Recently, the customer structure and their expectations are changed in the airline industry same as the other service industries with changed conditions by technology, quality of living etc. Due to changing expectations for service quality and new market structure, airline companies will be able to provide a competitive advantage through meeting customers' expectations with high satisfaction and understanding the changing market. In this context, the aim of this study is identifying the determinants of airline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, we are also quite consistent with profiles that were used in similar studies on the Turkish airline industry. In previous studies, it has been observed that the airline consumer profile is mostly female, young, and highly educated (Ayodeji & Rjoub, 2021;Kaya & Gorkem, 2020;Şimşek & Demirbağ, 2017).…”
Section: Demographic Profile Of Respondentsmentioning
confidence: 97%
“…In addition, we are also quite consistent with profiles that were used in similar studies on the Turkish airline industry. In previous studies, it has been observed that the airline consumer profile is mostly female, young, and highly educated (Ayodeji & Rjoub, 2021;Kaya & Gorkem, 2020;Şimşek & Demirbağ, 2017).…”
Section: Demographic Profile Of Respondentsmentioning
confidence: 97%
“…Despite the SERVQUAL model, AIRQUAL was further adopted for assessing the airline's service quality. The AIRQUAL consisted of five notable dimensions; airline tangibles, terminal tangibles, personnel, empathy, and image (Suki, 2014;Demirbag and Demirbag, 2017;Farooq et al, 2018). More precisely, Bowen, Headley, and Lutte (1993) proposed the airline service quality rating tool 'Airline Quality Rating (AQR).…”
Section: Service Qualitymentioning
confidence: 99%
“…Reliability dispenses accurate, competent, and dependable services (Kubra & Orkun, 2017). According to Chege (2020), reliability indicators included providing services as promised, staff being sincere and dependable in handling service problems, performing service right the first time, and maintaining error-free records.…”
Section: Service Reliabilitymentioning
confidence: 99%